Listening comprehension difficulties in English language - Yuldashev Sherali Baratovich; Khujanova Mastura Ibodullayevna (Genius Journals, 2022)
In today's our modern world everybody accepts that listening is one of the most important skills in second language acquisition. When listening to a second language, many language students face listening difficulties. Second language learners have significant problems in listening comprehension because of the fact that schools pay more attention to structure, writing, reading and vocabulary. Listening is not important parts of many course books or syllabus and most teachers do not attach importance to listening while preparing their lesson plan. A great number of teachers believe that it will develop naturally within the language learning process and they will learn unconsciously. Actually there are number of listening barriers based on message, delivery, audience and environment. Teaching and drilling listening strategies ease students listening comprehension
Keywords: Listening comprehension; listening difficulties; listening strategies